MEMBANGUN IDENTITAS MEREK: KONSEP DAN PRAKTIK BAGI UMKM DI YOGYAKARTA - Wardhana, Daniel Yudistya; Chrismadian Noventa, Oscar; Novianto Hariwibowo, Ignatius; Yustino Setiawan, Wimpie; Indra Kristianto, Ignatius; Aribawa, Dwitya; Adyantari, Api; Yupanzara Dharomesz, Vonezyo; Desy Pramusiwi, Aloysia (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program is a collaboration between the Community Service Team of the Faculty of Business and Economics, Universitas Atma Jaya Yogyakarta (FBE UAJY) and the Socio-Economic Development Team (PSE) of Paroki St. Yusup Binta ran. The focus of the activities includes developing brand identity, creating a unique value proposition, and utilizing brands as a means of marketing communication to increase consumer purchase ng power. Through this approach, SMEs are encouraged to understa nd the strategic role of branding not only as a business identity, but also as an instrument to build trust, loyalty, and competitive advantage. With the right branding strategy, SMEs are expected to be able to strengthen their market position, increase their adaptability in the digital era, and create a positive image in the minds of consumers which has implications for increasing commitment to the brand. This program adopts Participatory Action Research (PAR) with a structu red implementation and based on actual needs, so that it is expected to have a direct impact on the development of SMEs and strengthen their competitiveness the increasingly competitive market dynamics.